The Effect of Teacher's Decision in the Learning Process to The Implementation of Merdeka Curriculum - Amalia, Ilmi Zakiah; Pambudi, Syukur; Nabila, Salma; Nuari, Dewandani Nahar; Susanto, Teguh Trianung Djoko; Supadi, Supadi (Jurnal Akuntabilitas Manajemen Pendidikan, 2023)
In 2022, the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) published an independent curriculum (Kurikulum Merdeka). The role of teachers in the curriculum is very important, including the decisions they make to implement the curriculum. Therefore, research is carried out using literature study methods to find out teacher decision making in the learning process in the implementation of an independent curriculum. Based on the results of the literature obtained, the authors analyze the results of the synthesis of research from five selected articles on decision making on independent curriculum learning activities. The results of the study synthesis are classified in four categories, namely (a) independent curriculum direction towards learning goals; (b) learning process in the implementation of an independent curriculum; (c) decision making in the learning process; (d) linkages of independent curriculum goals and learning processes in teacher decision making. It was found that in the learning process, the role of teachers was very important so that implementation took place effectively. Teachers as learning leaders must be able to make decisions about the learning process that is in line with the objectives of the curriculum.